The identification of the vibration control system parameters designed for continuous miner machines. (May 2017) - Mężyk, Arkadiusz; Klein, Wojciech; Pawlak, Mariusz; Kania, Jan
Abstract: The Continuous Miner machines are exposed to time dependent loads during normal operation of the rock cutting process. These loads cause vibrations, which have a negative influence on the whole structure of the machine. This phenomenon can be eliminated by applying passive or active vibration control systems (VCS). Generally these systems are coupled with additional elements, which provide dispersion or transfer energy. The energy thus acquired can also reinforce the intended function such as rock cutting operation in the case of mining machines. The objective of this paper is to present the method of numerical identification of VCS parameters for Continuous Miner machines. The main function of the presented system is to reduce displacement of cutting drum by using elastic element joined to machine chassis and applying appropriate algorithm of control of the angular velocity of cutting drum. The method described improves efficiency of mining and increases durability of machine. In order to determine mechanical and control parameters of VCS the genetic algorithm optimisation method conjugated with numerical modal analysis was used. Finally the transient dynamic analysis was performed for the full-scale model of Continuous Miner in order to verify VCS in normal working condition. Highlights: We perform sensitive analysis of vibration control system parameters. We identification of vibration control system stiffness components by using genetic algorithms. We descript "flexibility factor" for analysis system. We define improved objective function which was used to identification process. We determine cutting forces by using non-linear finite element model.